2018
DOI: 10.1016/j.jacep.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Harmful Effects of Exercise Intensity and Exercise Duration in Patients With Arrhythmogenic Cardiomyopathy

Abstract: High-intensity exercise was a strong and independent marker of life-threatening VA in AC patients, independent of exercise duration. AC patients could be advised to restrict their exercise intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 27 publications
0
94
0
1
Order By: Relevance
“…Wang et al from the same research group reported a decreased risk for ventricular arrhythmias by reduced exercise dose (intensity × duration) in ARVD/C patients with and without desmosomal mutation [25]. Lie et al from Oslo University Hospital reported high-intensity exercise as a strong and independent marker of life-threatening ventricular arrhythmias in ARVD/C patients, independent of exercise duration [26].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al from the same research group reported a decreased risk for ventricular arrhythmias by reduced exercise dose (intensity × duration) in ARVD/C patients with and without desmosomal mutation [25]. Lie et al from Oslo University Hospital reported high-intensity exercise as a strong and independent marker of life-threatening ventricular arrhythmias in ARVD/C patients, independent of exercise duration [26].…”
Section: Discussionmentioning
confidence: 99%
“…Endurance training in AC patients, especially high intensity exercise, has been associated with VAs, more severe RV dysfunction, LV dysfunction, and heart failure [68,69]. Conversely, the risk of VAs and mortality can be reduced by lowering exercise [42,66,69,70]. A dose-dependent relationship between exercise exposure and the disease penetrance was demonstrated in different categories of AC patients.…”
Section: Impact Of Sports Activitymentioning
confidence: 97%
“…Kirchhof et al demonstrated that in heterozygous plakoglobin-deficient mice endurance training facilitated the development of RV abnormalities and VAs [67]. Endurance training in AC patients, especially high intensity exercise, has been associated with VAs, more severe RV dysfunction, LV dysfunction, and heart failure [68,69]. Conversely, the risk of VAs and mortality can be reduced by lowering exercise [42,66,69,70].…”
Section: Impact Of Sports Activitymentioning
confidence: 99%
“…Moreover, imaging studies revealed that left and right ventricular function was reduced and right ventricle volume enlarged in athletes when compared to non-athletes (Sen-Chowdhry et al, 2007). Interestingly, an apparent direct dose-response relationship has been established between exercise intensity and severity of AC phenotypes in AC-mutation carriers, where exercise intensity is more damaging than exercise duration (Lie et al, 2018a).…”
Section: Ac Penetrance Is Dependent On Physical Exercisementioning
confidence: 99%